2020
DOI: 10.1007/s10479-020-03523-w
|View full text |Cite
|
Sign up to set email alerts
|

Migrant supply chain networks: an empirically based typology

Abstract: Managing migrant supply networks is a critical issue both domestically and internationally. In this research, using a supply chain perspective, a typology is developed to provide recommendations for migration stakeholders. The typology can be used to assess factors within a migrant network including: pressure to migrate, the network agility, and the total cost of migration. The typology identifies specific investments that developmental agents can focus on to mitigate the pressure to migrate. In instances of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…This situation has been worse for people who live in immigration facilities or refugee camps. In this scenario, Italy is one of the European countries most impacted by this phenomenon, which is facilitated by some factors including: the pressure to migrate, the agility of the network and the total cost of migration (47). It has been demonstrated that a supra-national organization approach at the regional level is the most viable approach in the long term, with the ultimate goal of inter-regional cooperation on migration management based on equality between countries (48).…”
Section: Discussionmentioning
confidence: 99%
“…This situation has been worse for people who live in immigration facilities or refugee camps. In this scenario, Italy is one of the European countries most impacted by this phenomenon, which is facilitated by some factors including: the pressure to migrate, the agility of the network and the total cost of migration (47). It has been demonstrated that a supra-national organization approach at the regional level is the most viable approach in the long term, with the ultimate goal of inter-regional cooperation on migration management based on equality between countries (48).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, they may be understood as calculative devices that operationalize the rationality of finance (Callon & Muniesa, 2005). By monetizing qualitative factors, such as labour, commodities, and nature, they price risk as a means for accounting, strategic planning and speculative financing (Ouma et al, 2018;Pedraza-Acosta & Mouritsen, 2018;Prasad et al, 2020). These techniques of financial inclusion articulate persons and things within global value chains that reorganize relations of production and consumption as collateral for the expansion of credit and the accumulation of debt.…”
Section: The Bifurcation Of Global Governancementioning
confidence: 99%
“…Although stable networks depend on the agency, strong ties may result in family firm needs, which grow in a self-network as sources of transnational migration (Wu et al , 2022). Following Chung et al (2020), Crowley-Henry et al (2021), Daovisan and Chamaratana (2021), Hesketh and Box (2020) and Prasad et al (2022) mentioned that the network capital concept includes the source of capital, the mechanism of capital, the objective of capital and the impact of capital. Karayianni et al (2023) claimed that the network capital concept relates to interpersonal ties with family firms to drive transnational networks.…”
Section: Theoretical Lens and Contextmentioning
confidence: 99%